Pemanfaatan Teknologi Multimedia Sebagai Peningkatan Motivasi Pembelajaran Siswa Serta Keprofesionalisasian Guru - Jesi Alexander Alim; Adinda Quratul Aini; Gabriella Dameria Siregar; Risa Elyafatma Silaen (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this study was to determine the results of the use of multimedia technology regarding its effect on student learning motivation and teacher professionalism. The research method used in this study is library searching by searching for and collecting various other research sources to be studied in depth. The relationship between technological developments and the professionalism of a teacher provides a framework for understanding how important effective learning is in attracting students' interest in learning and understanding in the classroom. Technological developments in the form of using multimedia as a learning medium for students can be an effort to increase student learning motivation which in fact has a big influence on the professionalism of teaching staff. After using interactive multimedia, students' understanding increases. Students' motivation or enthusiasm for learning also increases so that the concepts of the learning material can be absorbed well.